United We (Net)work: An Analysis of Nigerian Women's clubs - (:unkn) unknown (My University, 2019)
This Research is part of the European Project PACKING (Protection of Migrants and Asylum seekers, especially Children and Women coming from Nigeria and victims of trafficking), conducted from 2017 and 2019, both in Nigeria and in France. PACKING Project is co-funded by the European Instrument for Democracy and Human Rights (EIDHR) of the European Union and is coordinated by the NGO ECPAT France. The general objective of the project is that rights of Migrants are promoted and respected and migrants are protected from trafficking in Human beings. This publication was elaborated with the support of European Union. The contents of this publication are the sole responsibility of ECPAT France and the partners of the project and can in no way be taken to reflect the views of the European Union.
Keywords: African Research